Differences in pedaling technique in cycling: A cluster analysis - Lanferdini, F. J.; Bini, R. R.; Figueiredo, P.; Diefenthaeler, F.; Mota, C. B.; Arndt, A.; Vaz, M. A. (International Journal of Sports Physiology and Performance, 2016)
Purpose: To employ cluster analysis to assess if cyclists would opt for different strategies in terms of neuromuscular patterns when pedaling at the power output of their second ventilatory threshold (POVT2) compared with cycling at their maximal power output (POMAX). Methods: Twenty athletes performed an incremental cycling test to determine their power output (POMAX and POVT2; first session), and pedal forces, muscle activation, muscle-tendon unit length, and vastus lateralis architecture (fascicle length, pennation angle, and muscle thickness) were recorded (second session) in POMAX and POVT2. Athletes were assigned to 2 clusters based on the behavior of outcome variables at POVT2 and POMAX using cluster analysis. Results: Clusters 1 (n = 14) and 2 (n = 6) showed similar power output and oxygen uptake. Cluster 1 presented larger increases in pedal force and knee power than cluster 2, without differences for the index of effectiveness. Cluster 1 presented less variation in knee angle, muscle-tendon unit length, pennation angle, and tendon length than cluster 2. However, clusters 1 and 2 showed similar muscle thickness, fascicle length, and muscle activation. When cycling at POVT2 vs POMAX, cyclists could opt for keeping a constant knee power and pedal-force production, associated with an increase in tendon excursion and a constant fascicle length. Conclusions: Increases in power output lead to greater variations in knee angle, muscle-tendon unit length, tendon length, and pennation angle of vastus lateralis for a similar knee-extensor activation and smaller pedal-force changes in cyclists from cluster 2 than in cluster 1.